Rancang Bangun Digitalisasi Formulir Perintah Kerja Berbasis Website dan Aplikasi Android dengan Metode Unified Modelling Language (UML) - Choirunnisa, Anis; Ardhianti Purna Murti, Zefanya; Fajrian, Rifki Alwi (Jurnal Instrumentasi dan Teknologi Informasi (JITI), 2025)
This study aims to design and build a website-based FPK digitalization system and android application in the Engineering Section. This system is designed as a solution to overcome the constraints of the manual system that has been used so far, such as process delays, risk of data loss, and cost and time inefficiencies. The methodology used in this study is the Agile method for software development and the Unified Modeling Language (UML) for system design, including Use Case Diagrams, Activity Diagrams, Sequence Diagrams, and Class Diagrams to describe the structure, workflow, and interactions between users comprehensively. Data collection was carried out through direct observation, literature studies, and historical data analysis such as the number of FPK usage and manual input time. The result of this study is an FPK digitalization system that involves four main actors, namely Admin, Section Head, Engineer, and Tenant. This system has main features that include Complain Form, Work Order, Approval, and Satisfaction Survey. Each user has different access and functions according to their respective roles. The conclusion of this study shows that the FPK digitalization system is able to increase work efficiency, reduce human error, reduce operational costs, and provide digital archives that are safer and easier to access.